The changing nature and role of vocational education and training in Europe ; VET in higher education: Country Case Studies : Case study focusing on Germany - Hippach-Schneider, Ute [Verfasser] (My University, 2018)
"The purpose of the Changing nature and role of VET-project is to improve our understanding of how VET is changing in the countries belonging to the European Union (as well as Iceland and Norway). Over a three-year period (2016-18) the project will analyse how vocationally oriented education and training has changed in the past two decades (1995-2015) and based on these results investigate the main challenges and opportunities facing the sector today and in the future. Work is divided into six separate but interlinked themes: (a) the changing definition and conceptualisation of VET; (b) the external drivers influencing VET developments; (c) the role of traditional VET at upper secondary level; (d) VET from a lifelong learning perspective; (e) the role of VET at higher education levels; (f) scenarios outlining alternative development paths for European VET in the 21st century. The study takes as its starting point that vocationally oriented education and training is something more than the traditional VET delivered at upper secondary level (in the form of school-based education or training, apprenticeships, or combinations of these). Due to the requirements of lifelong learning, we are able to observe diversification of VET with new institutions and stakeholders involved. We also see an expansion of VET to higher education areas, partly through reform of existing institutions, partly through the emergence of new institutions. This has been caused by factors internal to the education and training system as well as by external pressures linked to demographic, technological and economic changes. This particular case study, together with 9 other case studies, provides input to theme (b) of the project ('The external drivers influencing VET developments')." (excerpt; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 1.4 Hochschulbildung; S 1.3 Berufliche Erstausbildung; Berufsbildung; Berufsbildungspolitik; Berufseinmündung; Höhere Berufsbildung; Dualer Studiengang; Akademisierung